Integrating Sustainability Science in Maritime Vocational Education: Professional and Graduate Perspectives - Frisca Mareyta Pongoh; Iksan Saifudin; Aliong Silalahi; Jaya Alamsyah (Meteor STIP Marunda, 2025)
This qualitative study examines the effectiveness of sustainability integration in maritime vocational education through the perspectives of experienced professionals and recent graduates. Using semi-structured interviews with ten participants (five maritime industry experts and five recent graduates), the research investigates transdisciplinary competency development and educational-professional alignment within sustainability contexts. Thematic analysis reveals moderate effectiveness in current educational approaches, with a Professional Competency Integration Index (PCII) of 6.4 and an Educational-Professional Alignment Coefficient (EPAC) of 6.1 out of 10. While participants demonstrate strong theoretical foundations in environmental knowledge, significant gaps exist in practical integration skills, stakeholder engagement, and economic analysis capabilities. Both cohorts recognize the critical importance of sustainability integration but diverge in their assessment of educational adequacy: experienced professionals emphasize practical implementation challenges, while graduates focus on theoretical enhancement needs. The research identifies industry-education partnerships, transdisciplinary pedagogical approaches, and continuing education as critical factors for improving professional preparedness. Findings indicate that effective sustainability education requires the systematic integration of theoretical knowledge with practical application opportunities, supported by enhanced faculty development and comprehensive industry collaboration. The study provides evidence-based recommendations for maritime education transformation to address urgent environmental and regulatory pressures while supporting broader sustainability goals.